2014
DOI: 10.1371/journal.pone.0106598
|View full text |Cite
|
Sign up to set email alerts
|

Uniaxial Cyclic Stretch Promotes Osteogenic Differentiation and Synthesis of BMP2 in the C3H10T1/2 Cells with BMP2 Gene Variant of rs2273073 (T/G)

Abstract: Ossification of the posterior longitudinal ligament of the cervical spine (OPLL) is characterized by the replacement of ligament tissues with ectopic bone formation, and this result is strongly affected by genetic and local factors. Two single nucleotide polymorphisms (SNPs) of rs2273073 (T/G) and rs235768 (A/T) of bone morphogenetic protein 2 (BMP2) gene which are associated with OPLL have been reported in our previous report. In this study, we confirmed the connection in 18 case samples analysis of BMP2 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 45 publications
(44 reference statements)
0
13
0
Order By: Relevance
“…Likewise, variants in BMP-2 has been found to be involved in different stages of development of ectopic ossification 27 , such as Ser37Ala (T/G) (i.e., rs2273073, a relatively common SNP with MAF 0.03786 in ExAc) and Ser87Ser (A/G) (i.e., rs1049007, a common SNP with MAF 0.6723 in ExAc) 8 . As shown in a recent study, a forced expression of BMP2 containing the rs2273073 in C3H10T1/2 cells (mouse embryonic fibroblasts) was found to increase cell susceptibility to bone transformation similar to pre-OPLL change as well as the sensibility to mechanical stress which might play an important role during the progression of OPLL 28 . Therefore, what we observed an increased level of BMP2 with p.Q89E in the patient’s cells revealed its potential role in the pathogenicity of OPLL.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Likewise, variants in BMP-2 has been found to be involved in different stages of development of ectopic ossification 27 , such as Ser37Ala (T/G) (i.e., rs2273073, a relatively common SNP with MAF 0.03786 in ExAc) and Ser87Ser (A/G) (i.e., rs1049007, a common SNP with MAF 0.6723 in ExAc) 8 . As shown in a recent study, a forced expression of BMP2 containing the rs2273073 in C3H10T1/2 cells (mouse embryonic fibroblasts) was found to increase cell susceptibility to bone transformation similar to pre-OPLL change as well as the sensibility to mechanical stress which might play an important role during the progression of OPLL 28 . Therefore, what we observed an increased level of BMP2 with p.Q89E in the patient’s cells revealed its potential role in the pathogenicity of OPLL.…”
Section: Discussionmentioning
confidence: 65%
“…As shown in a recent study, a forced expression of BMP2 containing the rs2273073 in C3H10T1/2 cells (mouse embryonic fibroblasts) was found to increase cell susceptibility to bone transformation similar to pre-OPLL change as well as the sensibility to mechanical stress which might play an important role during the progression of OPLL28. Therefore, what we observed an increased level of BMP2 with p.Q89E in the patient’s cells revealed its potential role in the pathogenicity of OPLL.…”
Section: Discussionmentioning
confidence: 68%
“…Besides, both intronic polymorphisms involve changes in the recognition sites for transcription factors. In addition, these polymorphisms were previously reported in association studies of alleles related to bone disease . The BMP‐2 gene localization is 20p12.3.…”
mentioning
confidence: 72%
“…Several reports have showed that frequencies for the rs2273073 (T/G) and rs235768 (A/T) polymorphisms of BMP2 are significant higher in the OPLL than those in control groups. Both SNPs are associated with the occurrence of OPLL in Chinese Han population [ 52 - 55 ]. The functional analysis of rs2273073 (T/G) SNP has showed this mutant aberrantly activates BMP-Smad signaling.…”
Section: Opll Susceptibility Genes and Signalingmentioning
confidence: 99%
“…For example, transfection of this BMP2 mutant promotes the activation of p-Smad1/5/8, expression of Smad4 and activity of alkaline phosphatase (ALP) [ 55 ]. Uniaxial cyclic stretch promotes osteogenic differentiation and synthesis of BMP2 in the C3H10T1/2 Cells with BMP2 gene variant of rs2273073 (T/G) [ 52 ]. However, Kim et al reported that both BMP2 SNPs showed no significant difference between OPLL and non-OPLL groups in Korean populations [ 35 ].…”
Section: Opll Susceptibility Genes and Signalingmentioning
confidence: 99%